Martin Luther in context - Whitford, David M. ca. 20./21. Jh (Cambridge University Press, 2023)
Martin Luther remains a popular, oft-quoted, referenced, lauded historical figure. He is often seen as the fulcrum upon which the medieval turned into the modern, the last great medieval or the first great modern; or, he is the Protestant hero, the virulent anti-Semite; the destroyer of Catholic decadence, or the betrayer of the peasant cause. An important but contested figure, he was all of these things. Understanding Luther's context helps us to comprehend how a single man could be so many seemingly contradictory things simultaneously. Martin Luther in Context explores the world around Luther in order to make the man and the Reformation movement more understandable. Written by an international team of leading scholars, it includes over forty short, accessible essays, all specially commissioned for this volume, which reconstruct the life and world of Martin Luther. The volume also contextualizes the scholarship and reception of Luther in the popular mind